Endothelial Microparticle-Mediated Transfer of microRNA-19b Inhibits the Function and Distribution of Lymphatic Vessels in Atherosclerotic Mice - Yu, Shi-Ran; Cui, Yu-Xia; Song, Zi-Qi; Li, Su-Fang; Zhang, Chun-Ying; Song, Jun-Xian; Chen, Hong (Frontiers in Physiology, 2022)
In recent years, the function of the lymphatic system in atherosclerosis has attracted attention due to its role in immune cell trafficking, cholesterol removal from the periphery, and regulation of the inflammatory response. However, knowledge of the mechanisms regulating lymphangiogenesis and lymphatic function in the pathogenesis of atherosclerosis is limited. Endothelial microparticles (EMPs) carrying circulating microRNA (miRNA)s are known to mediate cell–cell communication, and our previous research showed that miRNA-19b in EMPs (EMPmiR-19b) was significantly increased in circulation and atherosclerotic vessels, and this increase in EMPmiR-19b promoted atherosclerosis. The present study investigated whether atherogenic EMPmiR-19b influences pathological changes of the lymphatic system in atherosclerosis. We first verified increased miR-19b levels and loss of lymphatic system function in atherosclerotic mice. Atherogenic western diet-fed ApoE-/- mice were injected with phosphate-buffered saline, EMPs carrying control miRNA (EMPcontrol), or EMPmiR-19b intravenously. The function and distribution of the lymphatic system was assessed via confocal microscopy, Evans blue staining, and pathological analysis. The results showed that lymphatic system dysfunction existed in the early stage of atherosclerosis, and the observed pathological changes persisted at the later stage, companied by an increased microRNA-19b level. In ApoE-/- mice systemically treated with EMPmiR-19b, the distribution, transport function, and permeability of the lymphatic system were significantly inhibited. In vitro experiments showed that miRNA-19b may damage the lymphatic system by inhibiting lymphatic endothelial cell migration and tube formation, and a possible mechanism is the inhibition of transforming growth factor beta receptor type II (TGF-βRII) expression in lymphatic endothelial cells by miRNA-19b. Together, our findings demonstrate that atherogenic EMPmiR-19b may destroy lymphatic system function in atherosclerotic mice by downregulating TGF-βRII expression.